MODUL WEYL SEBAGAI REPRESENTASI GRUP SIMETRI DARI PEWARNAAN SUATU GRAF - Intan Nisfulaila (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2022)
This research identifies the properties of Weyl module which had some similar properties with Specht module. Specht module as an irreducible representation of permutation module for some partition